FREQUENCY OF DEPRESSIVE SYMPTOMS IN PATIENTS WITH DIABETES MELLITUS - Nasir, Yamina; Khan, Qudsia Umaira (Pakistan Journal of Physiology, 2018)
Background: Co-morbid depression in diabetics is associated with hyperglycaemia, diabetic complications and poor compliance. Aim of study is to access the frequency of clinically relevant depressive symptoms in adults with type 1 and 2 diabetes and find their association with gender and age of the patient. Method: It was a cross-sectional study. The study was conducted in outpatient department of CMH Lahore for a period of six months. We included patients diagnosed with diabetes type 1 or 2 along with depressive symptoms. Any known case of depressive or personality disorder diagnosed before the onset of diabetes and those having a significant known medical history prior to/along with the development of diabetes were excluded from the study. Depression was gauged using Diagnostic and Statistical Manual of Mental Disorder-IV (DSM-IV) criteria. Chi square test was used to access the association between depression among diabetics with age and gender. Results: A total of 340 patients, 191 (56.2%) males and 149 (43.8%) females were included, out of which 304 (90.9%) qualified DSM-IV criteria for having depression. Out of 191 males, 160 presented with depressive symptoms whereas all female diabetics had depression. Chi-square value for gender association was 27 (statistically significant, p=0.000) and for age Chi-square value was 1.391, (statistically significant, p=0.014) with a peak at 55 years of age and a count of 40 patients. Conclusion: Presence of diabetes increases the frequency of depression along with significant association of age and gender of diabetics with co-morbid depression. Keywords: Diabetes mellitus, Depression, Hyperglycaemia, Co-morbid, Complications Pak J Physiol 2018;14(2):31–3